Rapid country assessment: Ethiopia: The impact of COVID-19 on the food system - de Roo, Nina; de Boef, Walter Simon (Wageningen University & Research, 2020)
Over the past months, governments and their health agencies have been trying to combat the spread of the COVID-19 pandemic with mobility restrictions and social-distancing measures. We value their efforts to protect people’s lives, health and livelihoods, as these measures contribute to a reduction in the likelihood of human mortality, severe health consequences and the spread of the disease, especially among vulnerable people and communities. However, these efforts have also resulted in challenges in the functioning of food systems in low- and middle-income countries. This rapid country assessment was set out to synthesise available secondary data in relation to the impact of the COVID-19 crisis and prioritise short-term challenges and actions required in Ethiopia. In this report we present the key impacts of the COVID-19 crisis on the food system, the effects of the lockdown measures on the most vulnerable groups, gaps identified in the data analysed and in government responses to the crisis, and actions required to address short-term priorities and challenges. The initial findings were reviewed by several experts.